A 1.8-V 6-bit 1.3-GHz flash ADC in 0.25-μm CMOS. - Uyttenhove, K. (IEEE Journal of solid state circuits)
The design and optimization of a high-speed low-voltage CMOS flash analog-to-digital converter (ADC) are presented. The optimization procedures used during the design give the needed specifications of the different building blocks. Also, an extensive description of the implemented digital error correction technique is described. The used analog power supply is only 1.8 V. The maximum sampling speed is 1.3 GHz. The signal-to-noise-plus-distortion ratio (SNDR) at 133 kHz is 33.2 dB, and the SNDR at 500 MHz is 32 dB. The total power consumption of the converter at full speed is 600 mW and the total active area is only 0.13 mm2. The ADC is implemented in a 0.25-μm pure digital CMOS technology.